2003
DOI: 10.1161/01.hyp.0000091821.39824.09
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II–NAD(P)H Oxidase–Stimulated Superoxide Modifies Tubulovascular Nitric Oxide Cross-Talk in Renal Outer Medulla

Abstract: Abstract-The source of superoxide (O 2 ⅐Ϫ) production and cell-to-cell interactions of O 2 ⅐Ϫ and nitric oxide (NO) in response to angiotensin II (AngII) were studied by fluorescence microscopic techniques to image rat renal outer medullary microtissue strips. Changes in intracellular O 2 ⅐Ϫ were determined by dihydroethidium-ethidium ratios, and NO was determined with 4,5-diaminofluorescein diacetate. AngII (1 mol/L) significantly increased O 2 ⅐Ϫ in the isolated, medullary thick ascending limb (mTAL). These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 28 publications
4
123
0
Order By: Relevance
“…NO produced in the TALH can diffuse into surrounding vasa recta capillaries to serve as a buffer against vasoconstrictors such as Ang II. 18 Ang IImediated increases in TALH superoxide production results in an attenuation of NO release, which decreases medullary blood flow and increases sodium reabsorption. It has previously been reported that superoxide-mediated decrease in NO crosstalk contributes to the decreased medullary blood flow observed in the hypertensive Dahl salt-sensitive rat.…”
Section: Discussionmentioning
confidence: 99%
“…NO produced in the TALH can diffuse into surrounding vasa recta capillaries to serve as a buffer against vasoconstrictors such as Ang II. 18 Ang IImediated increases in TALH superoxide production results in an attenuation of NO release, which decreases medullary blood flow and increases sodium reabsorption. It has previously been reported that superoxide-mediated decrease in NO crosstalk contributes to the decreased medullary blood flow observed in the hypertensive Dahl salt-sensitive rat.…”
Section: Discussionmentioning
confidence: 99%
“…62 When the juxtamedullary glomeruli are injured by hypertension, the impairment of oxygen delivery downstream from the vasa recta vessels would be expected to result in tubulointerstitial injuries in the outer medulla. Superimposed on these factors, a number of other elements, including neurohormonal factors, 56 inflammatory pathways, 53 oxidative stress 63,64 and tubular transport, 65,66 are involved in the pathogenesis of the injuries, among which tubulovascular crosstalk is of particular interest. 63,64,67,68 We have recently shown that an increase in tubular transport at the mTAL enhances superoxide production and reduces nitric oxide synthesis.…”
Section: Albuminuria and Endothelial Dysfunctionmentioning
confidence: 99%
“…Superimposed on these factors, a number of other elements, including neurohormonal factors, 56 inflammatory pathways, 53 oxidative stress 63,64 and tubular transport, 65,66 are involved in the pathogenesis of the injuries, among which tubulovascular crosstalk is of particular interest. 63,64,67,68 We have recently shown that an increase in tubular transport at the mTAL enhances superoxide production and reduces nitric oxide synthesis. [63][64][65]67 These changes would be transmitted to the neighboring vasa recta and would therefore facilitate vasoconstriction and reduction of medullary blood flow.…”
Section: Albuminuria and Endothelial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-agent signal capture was achieved by cycling at 3-s intervals between a 460-and 605-nm filter. Changes in O 2 ⅐ Ϫ were expressed as the ratio of ethidium:DHE fluorescence (26). The system used an Olympus IX70 fluorescence microscope equipped with dual photomultipliers (PMT, Photon Technology Int., Lawrenceville, NJ).…”
Section: Experimental Protocolmentioning
confidence: 99%